Concomitant chemo-radiotherapy for unresectable oesophageal cancer: A mono-institutional study on 40 patients - Torrente, Sara (2012)
BACKGROUND/AIM: To analyse clinical response, overall (OS) and disease free survival (DFS) and toxicity in patients with unresectable oesophageal cancer treated by concomitant chemo-radiotherapy (CRT). MATERIALS AND METHODS: Forty patients with stage IIa–IVa biopsy proven oesophageal carcinoma were treated with CRT. All patients were studied with endoscopy and CT and judged unresectable after multidisciplinary discussion. CRT consisted of 3 cycles of cisplatin 100 mg/m(2) or carboplatin 300 mg/m(2) on day 1 and 5-fluorouracil 1000 mg/m(2) as a continuous infusion of 96 h associated with concurrent 3D-conformal RT. By using 15 MeV X-rays, a total dose of 60–66 Gy was delivered with daily fractions of 1.8–2.0 Gy. RESULTS: Complete response (CR), partial response (PR) and no response (NR) were observed in 50%, 20% and 20% of cases, respectively. Of the 20 patients with CR, 15 developed loco-regional recurrent disease. OS and DFS rates at 3 and 5 years were 38%, 8%, 49% and 10%, respectively. Total radiation dose ≥60 Gy improved loco-regional control and complete response (CR vs. PR + NR; p = 0.004) influenced both DFS and loco-regional control. Grade 3 gastrointestinal and haematological acute toxicity occurred in 3/40 patients (7.5%). One patient developed grade 4 renal failure. Late toxicity was reported in 2/40 patients (5.0%), consisting of grade 3 radiation pneumonitis. CONCLUSIONS: Concomitant CRT for unresectable oesophageal cancer can result in an acceptable loco-regional control with limited toxicity. Response after treatment and total radiation dose influenced the outcome.